Design and development of wireless controller in CNC machining - Siti Nadhira, Mohammad Sunar (2013)
The computer numerical controlled (CNC) machines have become important element in manufacturing process development. The technology of the control CNC machining is not only for remote monitoring and adjustments in the production process only, but also the production plans are in line to be achieved. Wireless technologies can support both of the user needs and also provide the cost-effective solutions. This way, the initial solution for the engineers to use CNC (Computer Numerical Control) to run a manufacturing program is by using wireless controller. This wireless controller for CNC machine, using a concept that allow the user to sit at the computer (sometimes called client) and controls or remote the other computer machine (sometimes called Host) in different location without used any wire through it. This thesis is focus on controlling 3 axes controller and automated gripper controller during machining process in CNC machining. The project that assigns "Design and Development of a Wireless Controller for CNC Machining", it used a remote desktop application for Windows 7 and Windows XP. It is quite common for a remote desktop application to be used to control a host computer that is far from the client, connected only via the Internet. This project also used a Visual Basic programming in developing to control 3 axes and an automated gripper CNC machine. Program of controller 3 axes and automated gripper will be control by using execute programming method. Execution in computer and software engineering is the process by which a computer or a virtual machine such as CNC machine carries out the instructions of a computer program. Instructions in the wireless controller will trigger the sequences of 3 axes controller program action, to execute program in CNC machine. Those actions produce effects according to the instructions in the controller CNC machine program. From this project, the criteria in the selection aid focus in type of nature of control requirement by the application such as wireless controller for windows based and verify the wireless controller for CNC machining setup.